Neural Adjustments during Repeated Braking and Throttle Actions on a Motorcycle Setup - Marina, Michel; Torrado, Priscila; Duchateau, Jacques; Baudry, Stephane (International Journal of Sports Medicine, 2023)
The aim of the study was to assess neuromuscular changes during an intermittent fatiguing task designed to replicate fundamental actions and ergonomics of road race motorcycling. Twenty-eight participants repeated a sequence of submaximal brake-pulling and gas throttle actions, interspaced by one maximal brake-pulling, until failure. During the submaximal brake-pulling actions performed at 30% MVC, force fluctuations, surface EMG, maximal M-wave (Mmax) and H-reflex were measured in the flexor digitorum superficialis. At the end of the task, the MVC force and associated EMG activity decreased (P<0.001) by 46% and 26%, respectively. During the task, force fluctuation and EMG activity increased gradually (106% and 61%, respectively) with respect to the pre-fatigue state (P≤0.029). The Mmax first phase did not change (P≥0.524), whereas the H-reflex amplitude, normalized to Mmax, increased (149%; P≤0.039). Noteworthy, the relative increase in H-reflex amplitude was correlated with the increase in EMG activity during the task (r=0.63; P<0.001). During the 10-min recovery, MVC force and EMG activity remained depressed (P≤0.05) whereas H-reflex amplitude and force fluctuation returned to pre-fatigue values. In conclusion, contrarily to other studies, our results bring forward that when mimicking motorcycling brake-pulling and gas throttle actions, supraspinal neural mechanisms primarily limit the duration of the performance.
Keywords: power grip; forearm muscles; Hoffmann reflex; EMG activity; M-wave